A Critical Review of the Empirical Research of Transformative Learning (1999-2005) - Edward W. Taylor (Adult Education Research Conference, 2006)
This is a review of transformative learning (TL) since 1998 involving 40 empirical studies. Findings include trends of less emphasis on identifying transformative experiences in different setting, and more about fostering TL and better understanding the nature of critical reflection, relationships, a perspective transformation, and context. Also, research designs are becoming more sophisticated.
Keywords: Transformative learning; literature review; adult learning